Sisi Lain Pengadaan Barang dan Jasa dalam Sebuah Studi Dramaturgi - Putri Harziani; Made Sudarma; Aji Dedi Mulawarman (Universitas Trunojoyo Madura, 2017)
This study aims to explore the role of the actors involved in the procurement’s stage in Y’s Faculty of X’s University. The role of procurement personnel became main part of the show to see whether the procurement of goods and services in the Y’s Faculty that using direct procurement’s method have appropriate with the rules of Presidential Decree 70 of 2012. The Procurement’s stage is divided into the front stage and back stage that can not be separated in the show. Dramaturgy used as a method to analyze the role, coupled with using impression management’s analysis from John and Pittman Taxonomy. This research resulted in the conclusion that the procurement’s procedure has been carried out, although not fully follow the rules, because there are some procurement’s procedure were not met. Formal evidence is documented but not complete sequence and presented. Impression management techniques used by the actor to display the desired self-image, on time and under certain conditions.